The little red hen : (a play) - Rose, Gerald (Cambridge, UK ; New York : Cambridge University Press, 2004)
The little red hen finds none of her lazy friends willing to help her plant, harvest, or grind wheat into flour, but all are eager to eat the bread she makes from it. Presented in play format.
Keywords: Folklore; Animals -- Folklore